2013
DOI: 10.1563/aaid-joi-d-12-00242
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical and Histologic Outcome of Dental Implant in Large Ridge Defect Regenerated With Alloplast: A Randomized Controlled Preclinical Trial

Abstract: A basic tenet of successful osseointegration is that the implant resides in a sufficient quality and quantity of bone to ensure bone contact and thus stabilization. A prospective, randomized controlled preclinical trial was conducted to evaluate the bone-to-implant contact (BIC) when placing implants in bone regenerated by 3 different combinations of biphasic calcium phosphate (BCP). Dental implants were placed into the regenerated ridges of 6 female foxhounds; the ridges were reconstructed with different form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…OSTEON ™ II Collagen is intended to be used for dental applications, including ridge augmentation, extraction socket grafting, cystic cavities, and periodontal defects. The product has a moldable property, so that it can accommodate any shape or form [63]. …”
Section: Commercially Available Mineralized Collagen Productsmentioning
confidence: 99%
See 2 more Smart Citations
“…OSTEON ™ II Collagen is intended to be used for dental applications, including ridge augmentation, extraction socket grafting, cystic cavities, and periodontal defects. The product has a moldable property, so that it can accommodate any shape or form [63]. …”
Section: Commercially Available Mineralized Collagen Productsmentioning
confidence: 99%
“…Preclinical trials showed that a mineralized collagen composed of biphasic calcium phosphate (HA/β-TCP) and collagen were able to stimulate new bone formation in reconstruction of deficient alveolar ridges for dogs [63,79]. …”
Section: Clinical Applications Of Mineralized Collagen Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Collagenated biphasic calcium phosphate (CBCP) has recently received attention in the dental field [ 4 21 ]. As a bone substitute, CBCP shares the same basic characteristics of biphasic calcium phosphate (BCP), and exhibits comparable bone-regenerative potential [ 22 23 ]. As a carrier for rhBMP-2, the effectiveness of both BCP and CBCP has been demonstrated independently in several animal studies [ 3 4 21 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…26 Biphasic calcium phosphate (BCP) is frequently chosen for preventing flap collapse and carrying EMD in a clinical setting. 27,28 BCP has been demonstrated to have excellent osteoconductivity in various defects, [29][30][31] and its porous surface has advantages with respect to absorbing proteins and cell attachment. 32,33 The aim of this study was to determine the bone regenerative potential of EMD around dental implants in an in vivo animal model.…”
mentioning
confidence: 99%